2021
DOI: 10.3389/fimmu.2021.661241
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolism: Towards a Better Understanding the Mechanism of Parasitic Infection and Immunity

Abstract: As a relatively successful pathogen, several parasites can establish long-term infection in host. This “harmonious symbiosis” status relies on the “precise” manipulation of host immunity and metabolism, however, the underlying mechanism is still largely elusive. Immunometabolism is an emerging crossed subject in recent years. It mainly discusses the regulatory mechanism of metabolic changes on reprogramming the key transcriptional and post-transcriptional events related to immune cell activation and effect, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 133 publications
0
19
0
Order By: Relevance
“…In addition, the emerging immunometabolism, provides a novel insight on addressing these scientific puzzles mentioned above. Accumulating evidence has indicated that helminth or its derived molecules can reprogram the metabolic events in macrophages of host, thereby modulating the anti-infective immunity and providing a moderate living environment for the growth and development of helminth (163). Nevertheless, only sporadic mechanistic investigations in the view of immunometabolism have been reported (164,165).…”
Section: Summary and Prospectmentioning
confidence: 99%
“…In addition, the emerging immunometabolism, provides a novel insight on addressing these scientific puzzles mentioned above. Accumulating evidence has indicated that helminth or its derived molecules can reprogram the metabolic events in macrophages of host, thereby modulating the anti-infective immunity and providing a moderate living environment for the growth and development of helminth (163). Nevertheless, only sporadic mechanistic investigations in the view of immunometabolism have been reported (164,165).…”
Section: Summary and Prospectmentioning
confidence: 99%
“…Fatty acid oxidation may also be implicated in the regulation of the balance between effector T cells and Tregs ( 72 ). Indeed, fatty acid oxidation might promote generation of Tregs and inhibit polarization toward effector T cells ( 73 ).…”
Section: Immunometabolism In T Cellsmentioning
confidence: 99%
“…Recently published work indicated that S. japonicum infection caused the reprogramming of glucose and lipid metabolism in the liver of S. japonicum-infected mice [32][33][34]. Interesting, we found that the expression of glycolysis-related genes (PFKFB3, HK2), and fatty acid oxidative-related gene (PPAR-γ) in the liver were also decreased significantly after depletion of peritoneal macrophages; while restored macrophages in the abdominal cavity resulted in increased metabolic genes (Figure S4B-D), suggesting that peritoneal macrophages might contribute to the maintenance of liver metabolic homeostasis.…”
Section: Peritoneal Macrophages Are Essential For Promoting the Liver...mentioning
confidence: 99%